ANALYSIS OF THE ROLE OF PSYCHOLOGICAL SAFETY AND LEARNING CLIMATE ON INCIDENT REPORTING BEHAVIOR - Ince Rosmini; Kosasih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Incident reporting is a crucial component of patient safety systems; however, underreporting remains a persistent issue in healthcare organizations. This study aims to analyze the effect of psychological safety and learning climate on incident reporting behavior among healthcare professionals. A quantitative approach with a cross-sectional design was employed, involving healthcare workers at Hospital X as respondents. Data were collected using structured questionnaires and analyzed using multiple linear regression. The results indicate that psychological safety has a positive and significant effect on incident reporting behavior, suggesting that individuals are more likely to report incidents when they feel safe from blame or negative consequences. Learning climate also shows a positive and significant effect, indicating that a supportive environment that promotes learning and non-punitive responses to errors enhances reporting practices. Simultaneously, both variables significantly influence incident reporting behavior. The coefficient of determination (R²) shows that 50.7% of the variation in reporting behavior can be explained by psychological safety and learning climate.